The Personality and Activity of A. I. Solzhenitsyn in Estimations of Figures of the Past and Contemporaries - Gennadii Nikolaevich Khrapkov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article is devoted to assessing the identity and work of Solzhenitsyn to accounting and analysis presented in the estimates of figures of the past and contemporaries in literature, journalism and science. Purpose - based on the existing reviews, analytical studies of Solzhenitsyn, to present the most objective characteristic of the personality of the writer and journalist, his goals to which he aspired and pursued in all his works, and the results that he achieved in the end throughout their life. For writing this article the author applied the following methods: comparative (comparison of existing estimates and views of supporters and opponents of Solzhenitsyn with the aim of identifying their similarities, differences, disadvantages), analytic (the desire to identify the causes, the factors that really influenced the whole course of the writer’s life), evolution (an attempt to trace the change and development of new traits in the character of the writer at various stages of his life). The result of this work is to assess both the positive aspects and disadvantages in the life and work of writer and public figure, and the desire to show who considered themselves Solzhenitsyn, and what is actually the purpose in life he sought to achieve. The results of this work allow to develop new theories and to give a completely new direction in the study of the life and work of a brilliant writer and public figure.